Improving Students’ Critical Thinking Skills Through Active Learning in IPAS Learning - Resti Dwi Shafrilla; Sati (Jurnal Elementaria Edukasia, 2026)
This study was conducted due to the low level of critical thinking skills among fifth-grade students at SD Negeri 5 Jungjang in IPAS learning. Critical thinking is one of the essential competencies required in the 21st century and needs to be developed through active learning. This study aimed to improve students’ critical thinking skills through active learning in IPAS learning. The research employed Classroom Action Research (CAR) using the Kemmis and Taggart model, which was conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 20 fifth-grade students. Active learning was implemented through the Project Based Learning (PjBL) model, which encouraged students to actively investigate problems, collaborate with peers, and develop project-based solutions. Data were collected through observation and tests and analyzed using qualitative and quantitative techniques. The results showed an improvement in students’ critical thinking skills. In the pre-cycle, only 20% (4 students) achieved the expected criteria. The percentage increased to 60% (12 students) in Cycle I and reached 95% (19 students) in Cycle II. These findings indicate that active learning effectively improves students’ critical thinking skills in IPAS learning. Therefore, active learning can be used as an alternative learning approach to foster critical thinking skills in elementary schools.